Foraging ecology of Eurasian lynx populations in southwest Asia: Conservation implications for a diet specialist - Mengüllüoğlu, Deniz; Ambarlı, Hüseyin; Berger, Anne; Hofer, Heribert (Freie Universität Berlin, 2018)
Intraspecific variation in key traits of widespread species can be hard to predict, if populations have been very little studied in most of the distribution range. Asian populations of the Eurasian lynx (Lynx lynx), one of the most widespread felids worldwide, are such a case in point. We investigated the diet of Eurasian lynx from feces collected Mediterranean, mixed forest‐steppe, and subalpine ecosystems of Turkey. We studied prey preferences and functional responses using prey densities obtained from Random Encounter Modelling. Our analysis revealed that the main prey was brown hare (Lepus europaeus) in all three areas (78%–99% of biomass consumed) and lynx showed a strong preference for brown hare (Chesson's selectivity index, α = 0.90–0.99). Cannibalism contributed at least 5% in two study areas. The type II functional response of lynx populations in Turkey was similar to the Canada lynx (Lynx canadensis) and daily food intake in grams per lynx matched that of Canada lynx and Iberian lynx (Lynx pardinus), both lagomorph specialists, rather than those of Eurasian lynx from Europe. Therefore, lynx in Turkey may be better described as a lagomorph specialist even though it coexists with ungulate prey. We suggest that ungulate‐based foraging ecology of Eurasian lynx in Europe may be a recent adjustment to the availability of high densities of ungulates and cannot be representative for other regions like Turkey. The status of lagomorphs should become an essential component of conservation activities targeted at Eurasian lynx or when using this species as a flagship species for landscape preservation.